METHOD FOR EXPRESS DIAGNOSTICS OF RESONANT PROPERTIES OF WOOD AGED IN BUILDINGS - Ilyich Fedyukov, Vladimir; Sergeyevna Chernova, Maria (Journal of Applied Engineering Science, 2020)
New method and technical solutions for nondestructive express diagnostics and targeted selection of spruce wood with unique dendro-acoustic properties aged in buildings are presented. Flow charts of equipment and ways of its application to identify resonant properties of wood in different parts of a building, including the walls made of round timbers, ceiling and fl oor boards are given. The proposed ways of wood quality diagnostics in buildings has its advantages over conventional methods.